Patient Satisfaction: IT, CRM, Facilities, Price Impact in Hospital Setting.: Kepuasan dan Kesetiaan Pasien: Dampak Teknologi Informasi, Manajemen Hubungan Pelanggan, Fasilitas, dan Harga di Lingkungan Rumah Sakit - Suci Suryadini; Sriyono (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the influence of Information Technology, Customer Relationship Management, Facilities, and Price on patient satisfaction, with patient loyalty as an intervening variable, within the context of DKT Hospital in Sidoarjo. Employing a quantitative approach, data was collected from 100 patients through purposive sampling. Structural Equation Modeling using Partial Least Squares (SEM-PLS) was employed for data analysis. The findings reveal that Information Technology, Customer Relationship Management, Facilities, and Price significantly affect patient satisfaction. Additionally, Information Technology and Customer Relationship Management have a direct impact on patient loyalty. The study underscores the significance of these factors in healthcare management and their implications for enhancing patient satisfaction and loyalty, thereby contributing to the improvement of healthcare services. Highlights: The study explores factors influencing patient satisfaction and loyalty in a hospital setting. Information Technology and Customer Relationship Management play pivotal roles in shaping patient experiences. Findings provide insights for healthcare providers to enhance service quality and patient retention. Keywords: Healthcare Management, Patient Satisfaction, Patient Loyalty, Information Technology, Customer Relationship Management